Memaknai Ucapan Syukur dan Doa Paulus untuk Jemaat Filipi (Filipi 1:3-10) Implikasi untuk Hidup Bersyukur di Tengah Kesulitan - Elsa Herawati Lubis; Yosua Altiel Siburian; Patricia Dwi Irwani Telaumbanua (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Giving thanks in success is a natural and important part of a believer's life, especially when life is filled with abundance. However, the ability to remain grateful in the midst of failures and difficulties is a challenge in itself that tests the firmness of faith. In his letter to the Philippians, the Apostle Paul provides an example and an important message on how to remain grateful to God, even when he himself faced prison and suffering. This paper aims to explore the deep meaning of thanksgiving based on Philippians and how it can be applied in the daily lives of believers. Using a descriptive approach and relying on the Bible as the main source, this study reveals that Paul taught four main dimensions of thanksgiving: thanksgiving in suffering, thanksgiving in service, thanksgiving for Christ, and thanksgiving for God's blessings. True thanksgiving comes from a deep relationship with God, which enables one to remain steadfast in the midst of life's challenges. These principles become relevant to help believers live life with a grateful heart, both in easy and difficult circumstances, and find true peace in their faith journey.